Setting up and running a small-scale cooking oil business - Axtell, Barrie; Fellows, Peter (Technical Centre for Agricultural and Rural Cooperation, 2012)
The result of a collaborative effort by small business owners and advisers in ACP countries, this manual covers everything you need to know about starting up and managing a small-scale cooking oil business. Helpfully illustrated with numerous tables, checklists and case studies, it highlights important aspects such as production, processing and quality control. Marketing, packaging, branding and customer care are also covered, along with invaluable advice on how to plan and manage finances.